Investigating the lateralisation of experimentally induced auditory verbal hallucinations - Mak, Olivia; Couth, Samuel; Plack, Christopher J.; Kotz, Sonja A.; Yao, Bo (Frontiers in Neuroscience, 2023)
Auditory verbal hallucinations (AVHs), or hearing non-existent voices, are a common symptom in psychosis. Recent research suggests that AVHs are also experienced by neurotypical individuals. Schizophrenia patients with AVHs and neurotypicals who are highly prone to hallucinate both produce false positive responses in auditory signal detection. These findings suggest that voice-hearing may lie on a continuum with similar mechanisms underlying AVHs in both populations. The current study used a monaural auditory stimulus in a signal detection task to test to what extent experimentally induced verbal hallucinations are (1) left-lateralised (i.e., more likely to occur when presented to the right ear compared to the left ear due to the left-hemisphere dominance for language processing), and (2) predicted by self-reported hallucination proneness and auditory imagery tendencies. In a conditioning task, fifty neurotypical participants associated a negative word on-screen with the same word being played via headphones through successive simultaneous audio-visual presentations. A signal detection task followed where participants were presented with a target word on-screen and indicate whether they heard the word being played concurrently amongst white noise. Results showed that Pavlovian audio-visual conditioning reliably elicited a significant number of false positives (FPs). However, FP rates, perceptual sensitivities, and response biases did not differ between either ear. They were neither predicted by hallucination proneness or auditory imagery. The results show that experimentally induced FPs in neurotypicals are not left-lateralised, consistent with prior reports of reduced lateralisation in the speech perception of schizophrenia patients with AVHs. It supports the idea that AVHs may be a continuous phenomenon that varies in severity and frequency across the population. Studying induced AVHs in neurotypicals may help identify the underlying cognitive and neural mechanisms contributing to AVHs in individuals with psychotic disorders.